NEW FACILITIES OF THE MGSmodeller - F. V. Kazantsev; I. R. Akberdin; N. L. Podkolodnyy; V. A. Likhoshvai (Вавиловский журнал генетики и селекции)
Mathematical modeling and analysis of complex molecular-genetic systems (MGS) are the key challenges in the systems biology era. To solve this task the special technologies and programming approaches considering the MGS as an ensemble of dynamic interconnected subsystems with a more simple structure are necessary to be developed. We have presented the approach that is aimed at acceleration of reconstruction of the complex MGS mathematical models and complex analysis using high performance computation techniques.